The result of surgical treatment in patients with cerebral aneurysms in Maharaj Nakorn Chiang Mai Hospital: A report of 225 cases - Wanarak Watcharasaksilp (2018)
Objective: Evaluate the result of intracranial aneurysm surgery in Maharaj Nakorn Chiang Mai Hospital. Material and Method: A retrospective study of patients who underwent surgery for intracranial aneurysms between 2003 and 2007. The patients' age, gender, signs and symptoms, CT brain findings, Subarachnoid hemorrhage (SAH), World Federation of Neurosurgical Society grading (WFNS), and aneurysm location were studied and correlated with outcome after surgery. Results: Two hundred twenty five patients of intracranial aneurysm were operated on between 2003 and 2007. Two hundred nine patients (92%) had anterior circulation aneurysms and 18 (8%) had posterior circulation aneurysms. The outcome, as evaluated by Glasgow Outcome Scale (GOS), showed good recovery and moderate disability patients (142, 62.9%) were classified as favorable outcome group whereas patients with severe disability, vegetative state, and dead (83, 36.9%) were classified as unfavorable outcome. According to WFNS grading, the patients with unruptured aneurysm and WFNS grade 1-2 had favorable outcome in 116 patients (78.37%) and unfavorable outcome in 32 patients (21.62%). Whereas the patients with WFNS grade 3-5 had favorable outcome in 32 patients (33.76%) and unfavorable outcome in 51 patients (66.23%). Conclusion: This study of 225cases revealed 142 cases with favorable outcome and 83 cases with unfavorable outcome. Factors that affected the outcome were WFNS grading and age.